ISLAM MODERAT DAN RADIKALISME (KAJIAN TEORITIS TENTANG AYAT-AYAT RADIKALISME DALAM PRESPEKTIF ISLAM MODERAT) - Arif Budiono; Muhammad Ariful Hakim (MIYAH : Jurnal Studi Islam, 2018)
Abstrak: The discourse of radicalism in every religion always presents the name of God. This is understandable because religion has a strong authority over other forces, including Islam which from the very beginning declared itself a religion full of peaceful values, its teachings by some people are often used as a justification for various acts of violence. One of the causes is a misunderstanding of the verses of the Qur'an and also the hadith of the Prophet about jihad and qital. This paper intends to examine these verses by paying attention to their meaning and historical context so as to produce a correct and comprehensive understanding. The results of the study conclude that jihad and qital (war) in the Qur'an are different from acts of radicalism. The main goal of jihad is human welfare and not warfare. Thus, jihad is the duty of every Muslim throughout his life, while qital is conditional, temporal, and as a last resort after there is no other way but physical resistance. In addition, the implementation of war must meet various very strict requirements. Keyword: Radicalism, Jihad, Qital, Islamic Moderate